(untitled) (Journal of Business and Economics, 2025)
The adoption of digital currencies, including central bank digital currencies (CBDCs) and cryptocurrencies, represents a significant shift in the global financial landscape, with profound economic implications for both developed and developing economies. This review examines the economic consequences of digital currency adoption, focusing on its impact on monetary policy, financial stability, payment systems, and economic growth. By analyzing existing literature, policy reports, and empirical studies, the review highlights both the potential benefits and risks associated with integrating digital currencies into national and international financial systems.Findings indicate that digital currencies can enhance the efficiency, speed, and security of payment systems, reduce transaction costs, and promote financial inclusion by extending access to banking services for unbanked and underbanked populations. The literature also suggests that digital currency adoption can strengthen monetary policy implementation by providing central banks with improved tools for liquidity management, interest rate control, and macroeconomic monitoring. Furthermore, digital currencies may facilitate cross-border transactions and trade, thereby enhancing economic integration and international financial connectivity.However, the adoption of digital currencies also presents significant challenges and risks. The literature emphasizes concerns related to financial stability, including potential disruptions to commercial banking, increased volatility in cryptocurrency markets, and cybersecurity vulnerabilities. Regulatory uncertainty, legal frameworks, and the risk of illicit financial activities remain major hurdles, particularly in economies with underdeveloped financial infrastructure. Additionally, the literature notes that the economic effects of digital currency adoption are highly context-dependent, influenced by institutional capacity, technological readiness, and the broader macroeconomic environment.In conclusion, digital currency adoption has the potential to transform economic systems, offering opportunities for efficiency, inclusion, and improved monetary policy, while simultaneously posing risks to financial stability and regulatory governance. This review underscores the need for carefully designed strategies, robust regulatory frameworks, and ongoing empirical research to maximize the benefits of digital currencies and mitigate associated risks, ensuring their sustainable integration into the global economy.